Keeping America's military edge. - Carter, Ashton B. (Foreign Affairs)
The U.S. military's global dominance may be slipping. The armed forces themselves are still strong, but bad management and low morale have undermined America's security establishment. Unless the new president addresses globalization, commercialization, and information revolutions by transforming the operations of the American defense establishment, the nation's military dominance may eventually wane. Management reforms must focus on giving the national security establishment an advantage in new missions, maintaining an edge in areas of established superiority, and implementing revolutionary business practices in places where defense management has long underachieved.